Can You Develop New Interests? an Improved Instrument for Measuring Implicit Theories of Interest Development - Jahner, Erik Erwin (Frontiers in Education, 2021)
O’Keefe et al. (2018) did not sufficiently narrow the implicit theory-of-interest development to accurately address the targeted domain: potential development of an entirely new interest. This was revealed when current participants expressed alternative interpretations of the word “change” in the indicator’s stem. This study, therefore, sought to first characterise a way to think about implicit theories of interest and refine the wording. However, the revised items revealed low reliability in a targeted population of Singaporeans. Was this due to the manipulation of the questions or the new test population? This was evaluated by following the same sampling procedure as O’Keefe et al. (2018) and participants were presented with both the revised and the original versions of the items. Factor analysis revealed a preferred factor structure for both versions having potential implications for understanding implicit theories, as well as the dimensions of implicit theories-of-interests specifically.